Note: This is a crosspost from http://math.stackexchange.com; the original question may be found here.

I have a question regarding a script by Greg Lawler on Bessel processes:


There I encounter difficulties in understanding the last sentence on page 2.

Let $ W_t = (W_t^1,\dots,W_t^d) $ be a (standard) d-dimensional Brownian motion and

$$ X_t = |W_t| = |W_t|_2 = \left(\sum\limits_{j=1}^d \left(W_t^j\right)^2\right)^{1/2} $$

its (Euclidean) norm.

Now it is noted:

$$ dX_t^2=\sum_{j=1}^d d[(W_t^j)^2] = 2\sum_{j=1}^d W_t^j dW_t^j + d \;dt $$

and we are supposed to be allowed to write the later as

$$ dX_t^2 = d \; dt + 2X_t dZ_t $$


$$ Z_t = \sum_{j=1}^d\int_0^t\frac{|W_s^j|}{X_s} dW_s^j .$$

It is not clear to me why we may rewrite it like that. I think

$$ X_t dZ_t = \sum_{j=1}^d |W_t^j| dW_t^j $$ holds true.

Wouldn't this imply, e.g.,

$$ |W_t^1| dW_t^1 = W_t^1 dW_t^1? $$

But this is not true, is it? Do I have a lapse of thought here?

Thank you for any hints :)

Edit: So on SE someone suggested the $|\cdot|$ in the definition of $Z_t$ to be a typo. That is also what I was thinking lately.


Here is another way to arrive at the result. Set $Y_t = X_t^2$ (for clarity). As the OP shows, $$ dY_t = d \; dt + 2 \sum_{j=1}^d W_t^j dW_t^j \;, \quad Y_0 = x > 0 \;. $$ By definition of the infinitesimal generator of $Y_t$, we have \begin{align*} L f(x) &= \lim_{t \to 0^+} \frac{1}{t} \mathbb{E}_x \left\{ f(Y_t) - f(x) \right\} \\ &= d \; f'(x) + f''(x) \lim_{t \to 0^+} \frac{2}{t} \sum_{j} \mathbb{E}_x \left\{ \left( \int_0^{t} W_s^j dW_s^j \right)^2 \right\} \\ &= d \; f'(x) + f''(x) \lim_{t \to 0^+} \frac{2}{t} \sum_{j} \mathbb{E}_x \left\{ \int_0^{t} (W_s^j)^2 ds \right\} \\ &= d \; f'(x) + f''(x) \lim_{t \to 0^+} \frac{2}{t} \mathbb{E}_x \left\{ \int_0^{t} Y_s ds \right\} \\ &= d \; f'(x) + 2 x \; f''(x) \end{align*} where we used a Taylor series in $f$ about $t=0$ and the Itô isometry. With a slight abuse of notation, this $L$ implies that $Y_t$ is a weak solution of the SDE: $$ d Y_t = d \; dt + 2 \sqrt{Y_t} \; dZ_t $$ where $Z$ is a one-dimensional Brownian motion, and by Itô's formula, $X_t = \sqrt{Y_t}$ satisfies: $$ d X_t =\frac{d-1}{2 X_t} \; dt + dZ_t \;, \quad X_0 = \sqrt{x} \;. $$


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.